Radiological outcomes of femoral head resection in patients with cerebral palsy: a retrospective comparative study of two surgical procedures - Horsch, Axel; Hahne, Finja; Ghandour, Maher; Platzer, Hadrian; Alimusaj, Merkur; Putz, Cornelia (Children, 2021)
Background: We conducted this study to compare postoperative radiological outcomes of two surgical procedures (femoral head resection (FHR) and femoral head cap plastic surgery (FCP)) in patients with CP and hip dislocation. Methods: CP patients with Gross Motor Function Classification Score (GMFCS) IV or V, who underwent either FHR or FCP between 2007 and 2018 at Heidelberg University Hospital in Germany, were included. Most participants underwent postoperative traction in an attempt to prevent telescoping. Besides the above-mentioned objectives, we examined the association between telescoping and spasmolytic use, traction weight, and traction duration. Results: Thirty-eight CP patients were included, of whom 15 (25 hips) underwent FHR and 23 (30 hips) underwent FCP. Heterotopic ossification (grades I, II, and III) occurred in 80% and 83.3% of patients in the FHR and FCP groups, respectively. Telescoping occurred in 18.68 and 31.99% of patients in the FHR and FCP groups, respectively (p = 0.999). Other complications were similar between both groups. Conclusions: The postoperative outcomes of FHR and FCP are similar in terms of telescoping, heterotopic ossification, and complications. Although telescoping was encountered more in the FCP group, no significant difference from the FHR group was found. We noted that the weight of traction could reduce the development of telescoping.
Gesehen am 24.01.2022